The effectiveness of GuttaFlow Bioseal Obturation material in single rooted Mandibular Premolars: a scanning electron microscopy study - Mustaffa, Musliana; Zainal Abidin, Imran; Mohd Ibrahim, Mohamad Shafiq (Microscopy Society of Malaysia, 2022)
The effectiveness of obturation with GuttaFlow Bioseal is not clearly understood due to limited scientific evidence. This study aims to evaluate the material adaptation, sealer extrusion and duration taken for obturation. 30 single rooted extracted mandibular premolars were selected. Standard access cavity preparation was done and the root canals were prepared using endodontic rotary files. The samples were divided into 3 groups (n=10); continuous backfill, interrupted backfill and injectable groups. The obturation procedure was timed using a digital timer and the obturation radiograph was taken after procedure. The roots were sectioned horizontally at the apical, middle and coronal regions, then observed under scanning electron microscope (SEM) at 70x magnification. The SEM images were transferred to the SketchAndCalc Area Calculator software for evaluation of the material adaptation. There were no statistically significant differences in regard to the material adaptation at any level of evaluation and presence of sealer extrusion (P  0.05) in all techniques. Duration of obturation using the injectable technique was statistically significant shorter than the other techniques (P  0.05). The material adaptation and presence of sealer extrusion in all obturation techniques were comparable and the duration of obturation procedure using the injectable technique was slightly shorter.